2021
DOI: 10.1016/j.heliyon.2021.e06432
|View full text |Cite
|
Sign up to set email alerts
|

Study of microbiome changes in patients with ulcerative colitis in the Central European part of Russia

Abstract: Ulcerative colitis (UC) is an inflammatory disease that affects the colon and rectum. Recently, evidence has emerged about the influence of microbiota on the development of this disease. However, studies on the role of intestinal microbiota in the pathogenesis of UC have been incomplete. In addition, there are no comprehensive studies of the causes of ulcerative colitis and data on the microbiological composition of the intestines of patients with ulcerative colitis in Russia. We carried out a study of the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 55 publications
5
51
0
Order By: Relevance
“…Our findings also demonstrated that, in addition to increasing the abundance of Akkermansia , crocetin significantly reduced the abundance of Muribaculaceae_unclassified , Duncaniella , and Eisenbergiella , which were negatively correlated with colitis severity [ 32 , 33 ]. We found members of the family Muribaculaceae (known as S24-7) in the guts of homoeothermic animals, where they were thought to play an important role in modulating the host’s health by degrading mucin [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 82%
“…Our findings also demonstrated that, in addition to increasing the abundance of Akkermansia , crocetin significantly reduced the abundance of Muribaculaceae_unclassified , Duncaniella , and Eisenbergiella , which were negatively correlated with colitis severity [ 32 , 33 ]. We found members of the family Muribaculaceae (known as S24-7) in the guts of homoeothermic animals, where they were thought to play an important role in modulating the host’s health by degrading mucin [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, in patients with ulcerative colitis in the central European part of Russia, there was a significant decrease in the genus of Fusicatenibacte . The current research showed that the supplementation of XOS could increase the level of Fusicatenibacter , which may be beneficial for the UC treatment ( 31 ). Additionally, the number of Lactococcus and Lactobacillu s, increased under the supplementation of XOS ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 86%
“…It produces the design matrix where elements indicate whether a sample j belongs to the experimental group (clinically healthy cows or the group with subclinical mastitis) or not. p values for each OTU were obtained using the Wald test [ 24 ].…”
Section: Methodsmentioning
confidence: 99%